Pleiotropic effect of sodium-glucose cotransporter 2 inhibitors on blood pressure - Kao, Ting-Wei; Huang, Chin-Chou (Frontiers in Cardiovascular Medicine, 2022)
Sodium-glucose cotransporter 2 (SGLT2) inhibitors have been incorporated as guideline-directed medical therapy for heart failure with reduced ejection fraction. Recent trials clearly established the efficacy of SGLT2 inhibitors on cardiac remodeling while preventing renal function decline in patients with or without diabetes mellitus. Blood pressure reduction during SGLT2 inhibitors use has been proposed through pleiotropic pathways and as a potential contributor that translates to cardiovascular benefits. The mechanisms underlying this decrease in blood pressure are not simply glycemic control. Orchestrating fluid status, modulation of sodium content and renin-angiotensin-activation system, anti-fibrosis and anti-inflammatory effect, ameliorating the characteristics of metabolic syndrome, as well as restoration of circadian rhythm all contributed to the BP lowering effect by SGLT2 inhibitors. Although SGLT2 inhibitors has not been demonstrated as anti-hypertensive agents thus far, their effects on BP alteration are clinically significant. In this review, we revisited the evidence correlating SGLT2 inhibitor use with blood pressure level. Future research directions will focus on the signaling pathway of SGLT2 inhibitors for fluid removal, atherosclerosis, vasoconstriction, and eventually hypertension.